Hierarchical Analysis Method and Model Based Data of Controlling Parts of the Body for Clothing (Journal of Fiber Bioengineering and Informatics, 2014)
In order to study the accuracy of human measurement data more systematically, the analytic hierarchymodel was established to evaluate the degree of measurement difficulty. Based on the manual measurementexperiment, we extracted and analyzed the data from different angles, such as the proficiency of work,parts of human body, error correcting frequency and single factor. The three factors, difficulty ofrecognizing the defined points, dimension of the moving points and measuring path, are used as thestandard of criterion level. The results showed that the structure of the body's parts of is the key toproducing the measurement difficulty and the difficulty of recognizing the defined points is the most.Besides, shoulder width is the most difficult part to measure and the chest circumference is the least.